Prospectively ECG-triggered high-pitch 80 kVp coronary computed tomography angiography with 30 mL of 270 mg I/mL contrast material and iterative reconstruction. (March 2016) - Qi, Li; Wu, Sheng Yong; Meinel, Felix G; Zhou, Chang Sheng; Wang, Qing Qing; McQuiston, Andrew D; Ji, Xue Man; Schoepf, U Joseph; Lu, Guang Ming; Zhang, Long Jiang
Background: The smallest diagnostically appropriate amount of contrast medium should be used in coronary computed tomography angiography (CCTA). Purpose: To investigate the feasibility of prospectively ECG-triggered high-pitch CCTA using 30 mL of 270 mg I/mL contrast material, 80 kVp, and iterative reconstruction (IR). Material and Methods: Eighty-two consecutive patients underwent CCTA with a prospectively ECG-triggered high-pitch protocol. Forty-three patients were examined at 100 kVp with filtered back projection after 60 mL of 370 mg I/mL contrast material was administered. Another 39 patients were examined at 80 kVp with IR after 30 mL of 270 mg I/mL contrast material was administered. Subjective and objective image quality was evaluated for each patient. Radiation doses were estimated and compared. Results: Mean attenuation, noise and signal-to-noise ratio in 80 kVp group were significantly lower than in 100 kVp group (all P < 0.05), while there was no significant difference in contrast-to-noise ratio (CNR), although a trend towards a lower CNR in 80 kVp group was observed ( P = 0.099). The subjective image quality between the two groups was not significantly different ( P = 0.905). The effective dose and iodine load in 80 kVp group were reduced by 54% and 64%, respectively, when compared with 100 kVp group. Conclusion: Prospectively ECG-triggered high-pitch CCTA at 80 kVp with 30 mL of 270 mg I/mL contrast material and IR is feasible for patients with BMI less than 25 kg/m 2 and reduces radiation dose and iodine load when compared with the standard CCTA protocol.